Building on the EGIPPS performance assessment: the multipolar framework as a heuristic to tackle the complexity of performance of public service oriented health care organisations - Marchal, Bruno (BioMed Central, 2014)
BACKGROUND: Performance of health care systems is a key concern of policy makers and health service managers all over the world. It is also a major challenge, given its multidimensional nature that easily leads to conceptual and methodological confusion. This is reflected by a scarcity of models that comprehensively analyse health system performance. DISCUSSION: In health, one of the most comprehensive performance frameworks was developed by the team of Leggat and Sicotte. Their framework integrates 4 key organisational functions (goal attainment, production, adaptation to the environment, and values and culture) and the tensions between these functions. We modified this framework to better fit the assessment of the performance of health organisations in the public service domain and propose an analytical strategy that takes it into the social complexity of health organisations. The resulting multipolar performance framework (MPF) is a meta-framework that facilitates the analysis of the relations and interactions between the multiple actors that influence the performance of health organisations. SUMMARY: Using the MPF in a dynamic reiterative mode not only helps managers to identify the bottlenecks that hamper performance, but also the unintended effects and feedback loops that emerge. Similarly, it helps policymakers and programme managers at central level to better anticipate the potential results and side effects of and required conditions for health policies and programmes and to steer their implementation accordingly.